Aplikasi Syariat Dalam Bisnis - Hedher Tuakia (Akutansi Bisnis & Manajemen ( ABM ), 2018)
Today there is a transition point of view to the conception of business / business. Some businesspeople no longer rely solely on the economic system adopted by capitalism (conventional) but also begin to direct their point of view on the economic / business system that can give satisfaction to the spiritual aspects or the satisfaction of the human mind. The traders in running their business do not merely get the highest material benefits, but they also want to get satisfaction. This is indicated by the adamnya sense of satisfaction if ternayata in running the business can be beneficial to the surrounding environment and for the purposes of social interaction. be friendly and tolerant to others and want to establish brotherhood among fellow traders and the surrounding community. That the motive or intention of the merchants in his business is to seek the blessing or pleasure of Allah SWT. Not just to maximize profits, as adopted by the conventional economic system. They practice what Rasulullah SAW has exemplified in his business by always being honest, trustful and tolerant.